Long Term : Essays on Queer Commitment - Wallace, Lee, 1962-; Herring, Scott, 1976- (Book collections on Project MUSE., 2021)
"The tension between the popular embrace of same-sex marriage and the queer critique of homonormativity prompts the contributors to Long Term to explore queer commitments as they are more broadly conceived. The essays contained here de-familiarize the idea of commitment and extend the category of significant others to include animals, possessions, institutions and disciplines. Revitalizing the concerns of queer theory beyond the commitment to anti-normativity, these essays contribute to interdisciplinary scholarship in queer temporality studies, disability studies, autotheory, and the emergent sub-field of age studies. Long Term includes an introduction on notions of the long term and essays that specifically address a number of topics-the commitment to palliative care; long-term attachment and loss; long-term pharmaceutical use; the commitment to pets; fear of commitment and institutionalization; long-term debt and financialization; the racial dimensions of long-term incarceration and voluntarism; queer kinship and racialized reproductive technologies; serial commitment; and the commitment to friendship"--